2019
DOI: 10.1038/s41598-019-42848-w
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-based hydrogel to support the paracrine activity of mesenchymal stem cells in spinal cord injury treatment

Abstract: Advanced therapies which combine cells with biomaterial-based carriers are recognized as an emerging and powerful method to treat challenging diseases, such as spinal cord injury (SCI). By enhancing transplanted cell survival and grafting, biomimetic hydrogels can be properly engineered to encapsulate cells and locate them at the injured site in a minimally invasive way. In this work, chitosan (CS) based hydrogels were developed to host mesenchymal stem cells (MSCs), since their paracrine action can therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 54 publications
(59 reference statements)
6
71
0
Order By: Relevance
“…Among the different tools of regenerative medicine “stem cells” are considered the most promising due to their self-renewal capability and multi-differentiation potential. However, recent studies have shown that the positive outcomes of different types of stem cell-based regenerative therapies are not directly correlated to the engraftment of transplanted cells[ 2 , 3 ]. These findings have created a huge interest in the regenerative potential of paracrine factors and have led scientists to reveal the regenerative potential of proteins in the secretomes.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different tools of regenerative medicine “stem cells” are considered the most promising due to their self-renewal capability and multi-differentiation potential. However, recent studies have shown that the positive outcomes of different types of stem cell-based regenerative therapies are not directly correlated to the engraftment of transplanted cells[ 2 , 3 ]. These findings have created a huge interest in the regenerative potential of paracrine factors and have led scientists to reveal the regenerative potential of proteins in the secretomes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is a re-absorbable biomaterial whose degradation products (including chito-oligosaccharides) positively influence nerve regeneration ( Gong et al, 2009 ; Zhao et al, 2017 ). Furthermore, chitosan can be processed through many fabrication technologies ( Ruini et al, 2015 ; Tonda-Turo et al, 2017b ) to produce NGCs both as external wall material and cell-based therapies as internal filler ( Boido et al, 2019 ; Tonda-Turo et al, 2020 ). One factor limiting chitosan use as a nerve guide is its low mechanical strength; nevertheless, Freier et al (2005b) demonstrated that modifying the chitosan acetylation degree, its mechanical stability can be improved and conduits with different acetylation degree were also tested in vivo ( Haastert-Talini et al, 2013 ).…”
Section: Natural-based Biomaterialsmentioning
confidence: 99%
“…Chitosan is a kind of positively charged biopolymer compound rarely seen in nature. It has abundant sources, low price, non-toxicity, non-irritation, non-antigenicity, heat-source reaction, non-hemolysis, non-mutagenicity, natural degradation, good histocompatibility, and controlled-release effects ( Boido et al, 2019 ). In addition, during the treatment of SCI, chitosan has significant neuroprotective properties, maintains the integrity of the cell membrane, and can block the activity of lipid peroxidation ( Elizalde-Peña et al, 2017 ).…”
Section: Materials For Polymer Scaffoldsmentioning
confidence: 99%